From Moment to Movement: Empowerment and Resilience as a Framework for Collective Action in Hong Kong. Issue 1 (March 2017) - Chan, Wing Y.; Cattaneo, Lauren B.; Mak, Winnie Wing Sze; Lin, Wan‐Ying
Abstract: The Transconceptual Model of Empowerment and Resilience ( American Journal of Community Psychology, 52, 2013, 333) suggests that a set of resilience and empowerment resources fuel both initial and sustained participation in collective action. Using the case study of a prodemocracy movement in Hong Kong, the present study focused on the subset of those resources that are relevant in ongoing collective action: efficacy, skills, and maintenance. As individuals possess varying combinations of these resources, the present study utilized latent profile analysis to test how patterns of empowerment and resilience resources influence initial and long‐term collective action. Five groups were identified: (a) Uncommitted/Uninspired; (b) Committed to Status Quo; (c) Mainstream Populist; (d) Empowered; and (e) Ambivalent. ANOVA and ANCOVA analyses found that there are significant group differences in initial and long‐term participation. Groups with higher level of resources reported greater levels of initial participation than their counterparts; however, high resource groups did not uniformly report greater levels of intention to participate in future collective action. Of the maintenance processes tested, collective identity emerged as a particularly important predictor differentiating initial and sustained participation. Findings from the present study raise questions about how individuals with multiple identities can come together and participate in collective action. Highlights: Used latent profile analysis to examine impact of empowerment and resilience on collective action. Identified the relations between multiple collective identities and collective action. Sustained collective action requires coalition among different groups, including the oppressor.